Strategi Tata Kelola BUMDes dalam Upaya Menunjang Ekonomi Masyarakat di Desa Pamulihan Kecamatan Cisurupan Kabupaten Garut - Ayi Sofian (Universitas Serang Raya, 2021)
Village-Owned Enterprises (BUMDes) is a village economic institution that aims to help support driving the economy of rural communities. Pamulihan Village, where the majority of the people were farmers, really needed BUMDes in order to support and improve the village economy. The research objective was to analyze the level of participation of the Pamulihan Village Community in the existence of BUMDes in order to support village economic development. This research is a type of qualitative research with data collection techniques in the form of interviews and documentation. The results showed that 1) BUMDes Pamulihan Village had succeeded in giving a positive impact on improving the village economy and community welfare. 2) Management of BUMDES by the management is very orderly based on the regulations that have been set by the government, 3) BUMDES Pamulihan Village although not maximized in running its business units, based on the data collected, it was found that high community participation in welcoming the existence of BUMDes .